ASSESSMENT OF SOIL CHEMICALS INFLUENCING PERSISTENCE OF Clostridium perfringens IN THE SELECTED DISTRICTS OF PUNJAB PROVINCE, PAKISTAN - Saira Naureen; Masood Rabbani; Ali Ahmad Sheikh; Abu Saeed Hashmi; Bhushan M. Jayarao (Journal of Animal and Plant Sciences, 2026)
Clostridium perfringens (C. perfringens), a spore-forming anaerobic bacterium, is widely distributed in soil and poses a significant risk to humans, poultry and livestock by causing enteric infections. Its persistence in the environment is influenced by soil chemical composition; however, limited information is available on its prevalence and associated risk factors in Pakistan. This study aimed to determine the prevalence of C. perfringens in soil samples from nine districts of Punjab Pakistan, using real-time PCR and to evaluate the influence of key soil chemical parameters on its distribution. A total of 970 pooled soil samples (representing 2,425 individual samples) were collected from 485 villages, of which 96 (9.89%) tested positive for the presence of C. perfringens DNA. Soil chemistry analysis of positive and negative samples (n = 192) revealed a significant association (p ≤ 0.05) of C. perfringens prevalence with organic matter, nitrogen, calcium, sodium, potassium, magnesium, and manganese, while heavy metals such as lead, nickel, copper, and chromium exhibited an inverse association. Conversely, pH, soluble salts, phosphorus, zinc, and iron showed no significant correlation with pathogen occurrence. District wise variation revealed the highest prevalence was observed in Chakwal (18%), followed by Attock (13.33%) and Lahore (12%), whereas Faisalabad (7.40%) and Sargodha districts (6.75%) showed the lowest. The findings highlight the strong role of soil chemistry, particularly nutrient-rich environments, in promoting C. perfringens persistence, underscoring the need for improved land and livestock management strategies to reduce environmental transmission risks and associated disease outbreaks.
Keywords: Soil chemistry; micronutrients; Clostridium perfringens